DINAMIKA HAK WARIS ANAK ANGKAT DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Akhmad Rudi Maswanto; Surya Wulandari; Dwi Risqi Meilani (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2023)
This research was conducted with the aim of finding out how the inheritance rights of adopted children apply to the assets of their adoptive parents and how the inheritance distribution system is for these adopted children. By using normative juridical research methods, it can be concluded, in the event that the inheritance rights of adopted children occur due to the influence of legal pluralism in the civil field that applies in Indonesia. In the Islamic legal system, adoption does not carry legal consequences in terms of blood relations and inheritance relations with adoptive parents. In inheritance rights according to BW (Burgelijk Wetboek), this law does not regulate the inheritance rights of adopted children but contains the rights of each heir to a certain part of the inheritance by using the term Legitieme portie. Regulations regarding inheritance law that apply in Indonesia to date apply 3 legal systems, namely inheritance according to customary law, inheritance according to Islamic law and inheritance according to BW (Burgelijk Wetboek) whose enactment is based on the choice of law from the community. Inheritance arrangements according to customary law refer to the system that applies to each customary community. Inheritance arrangements according to Islamic Law refer to the Compilation of Islamic Law which regulates the distribution of inheritance according to the Compilation of Islamic Law (KHI). Inheritance arrangements in Civil Law comply with the provisions in BW (Burgelijk Wetboek).